Quest for education and the problems facing Sudanese students in the diaspora: the Malaysian scenario - Kadouf, Hunud Abia (World Association for Sustainable Development, 2017)
Malaysia has become a major destination for Sudanese youth particularly, for education purposes. There are, however, some impending social problems that have erupted therefore adversely affecting their existential relationship with the host society. The diversity ed nature of these problems has apparently transcended their entire expectations. This paper identites the increasing challenges and prevalent social problems among Sudanese youth in Malaysia and gives suggestions for mutual acceptance and tolerance.